The influence of serum Sterol Sulfotransferase, ANGPTL8, and SDC1 on liver function in patients with intrahepatic cholestasis during pregnancy: Serum Sterol Sulfotransferase, ANGPTL8, and SDC1 on liver function in intrahepatic cholestasis - Wang, Qixin; Wang, Ming; Wu, Wenqi (Journal of Medical Biochemistry, 2026)
[Objective] To explore the relationships between serum Sterol Sulfotransferase, Recombinant Angiopoietin Like Protein 8 (ANGPTL8), and Recombinant Syndecan (SDC1) and liver function in patients with intrahepatic cholestasis of pregnancy (ICP), as well as their influence on perinatal outcomes. [Methods] The control group consisted of 200 healthy pregnant women who had physical tests over the same time period, while the study group consisted of 210 ICP patients who were admitted to our hospital between June 2023 and December 2024. The study group’s and the control group’s serum Sterol Sulfotransferase, ANGPTL8, SDC1, and liver function markers were compared. Pearson correlation analysis was used to analyze the correlations between the levels of serum Sterol Sulfotransferase, ANGPTL8, and SDC1 and various liver function indicators. The patients in the study group were divided into a poor outcome group (86 patients) and a good outcome group (124 patients) according to perinatal outcomes. Serum Sterol Sulfotransferase, ANGPTL8, and SDC1 levels were examined between the groups with negative and positive outcomes. The factors predicting unfavorable perinatal outcomes in patients with ICPs were examined using univariate and multivariate logistic regression analysis. [Results] Despite having a lower serum Sterol Sulfotransferase level, the study group had higher levels of ANGPTL8 and SDC1 than the control group. P<0.05 indicated that the differences were statistically significant. The study group’s levels of alkaline phosphatase (ALP), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) were considerably higher than the control group’s (P<0.05). The findings of the Pearson correlation analysis showed that while the levels of ANGPTL8 and SDC1 were positively connected with the levels of AST, ALT, and ALP (P<0.05), the level of serum Sterol Sulfotransferase was adversely connected with these levels. Compared to the group that experienced a positive outcome, the unfavorable outcome group’s serum Sterol Sulfotransferase level was lower, whereas SDC1 and ANGPTL8 levels were greater than those in the group with favorable results. Decreased serum Sterol Sulfotransferase levels (≤23 μmol/L), increased ANGPTL8 levels (≥650 pg/mL), and poor perinatal outcomes were associated with elevated SDC1 levels (≥53 ng/mL) in patients with ICP (P<0.05). [Conclusion] Serum Sterol Sulfotransferase, ANGPTL8 and SDC1 are closely related to liver function and perinatal outcomes in patients with ICP. As the level of serum Sterol Sulfotransferase decreases and the levels of ANGPTL8 and SDC1 increase, it can lead to aggravated liver function impairment in patients with ICP, and it leads to adverse perinatal outcomes.